Circumferential Strain Analysis Identifies Strata of Cardiomyopathy in Duchenne Muscular Dystrophy: A Cardiac Magnetic Resonance Tagging Study - Hor, Kan N (2009)
OBJECTIVES: This study sought to evaluate the natural history of occult cardiac dysfunction in Duchenne Muscular Dystrophy (DMD). BACKGROUND: DMD is characterized by progressive cardiac dysfunction and myocardial fibrosis late in the disease process. We hypothesized that left ventricular myocardial peak circumferential strain (ε(cc)) would decrease in DMD prior to global systolic functional abnormalities regardless of age or ventricular ejection fraction (EF). METHODS: We evaluated cardiac magnetic resonance image (CMR) data from 70 DMD patients and 16 aged-matched control subjects. Standard imaging data included steady-state free precession (SSFP) short-axis cine stack images, cine myocardial tagged images and myocardial delayed enhancement (MDE, an indicator of myocardial fibrosis) sequences. Analysis was performed using QMASS® and HARP® softwares. DMD patient data was subdivided by age (< 10 years or > 10 years), EF (> 55% or <55%) and the presence or absence of MDE. RESULTS: DMD patients with normal EF had reduced ε(cc) at an early age (<10 years) compared to control subjects (p< 0.01). DMD patients >10 years with normal EF had further decline in ε(cc) compared to younger DMD patients (p<0.01). There was further decline in ε(cc) with age in patients with reduced EF (p<0.01) without MDE. The oldest patients, with both reduced EF and positive MDE, exhibited the lowest ε(cc). None of the patients had ventricular hypertrophy. CONCLUSIONS: Myocardial strain abnormalities are prevalent in young DMD patients despite normal EF, and these strain values continue to decline with advancing age. Strain analysis in combination with standard CMR and MDE imaging provides a means to stratify DMD cardiomyopathy.